Salmonella enterica serotypes and Salmonella infections: A multicenter study covering ten provinces in Turkey [Salmonella enterica serotipleri ve Salmonella enfeksiyonlari: Türkiye'de on ili kapsayan çok merkezli bir çalişma] - (:unkn) unknown (My University, 2004)
In order to find the distinctive features of Salmonellae and Salmonella infections in Turkey, 620 Salmonellae strains, isolated from various clinical samples (481 stool, 108 blood, 12 urine, 3 bone marrow, 3 cerebrospinal fluid, 9 pus, and one from each of the bile, pleural fluid, wound, catheter samples) in 13 clinical microbiology laboratories of 10 provinces in Turkey (Ankara, Antalya, Bursa, Edirne, Eskişehir, İstanbul, İzmir, Kayseri, Konya and Trabzon) between July 1, 2000 and June 30, 2002, were serotyped. Among the patients 43% were female, 57% were male, 63.2% were from outpatient clinics and 36.8% were hospitalized patients. Seventy eight percent of the patients had gastroenteritis, 10.7% had septicemia/local infection, 9.8% had typhoid/ paratyphoid fever and 1.5% were carriers. Incidence of gastroenteritis was higher in 0-5 years age group (p<0.001). Of the 620 Salmonella enterica isolates, 47.7% were S.Enteritidis, 34.7% S.Typhimurium, 6% S.Paratyphi B, 2.9% S.Typhi, 0.2% S.Paratyphi A, 6.1% serogroup C1, and 2.4% serogroup C2. S.Enteritidis was the most common serotype in all provinces except for Kayseri, where S.Typhimurium was found to be the most common serotype (68.2%). Overall, the most frequently isolated serotype was S.Enteritidis, also being the most common serotype in stool and blood cultures. During the surveillance period two outbreaks have occurred, the first one by S.Enteritidis strains in Edirne, and the second one by S.Typhimurium strains in Kayseri. As a result, Salmonella infections are still a common health problem in Turkey, and active surveillance of Salmonella infections has vital importance.
Keywords: Salmonella enterica serotypes; Salmonella infections